Efeito da crioterapia e da laserterapia na resposta ao dano muscular induzido pelo exercício excêntrico: ensaio clínico e randomizado - Macedo, Liane de Brito (2013)
Exercise-induced muscle damage mainly affects individuals who returned to physical activity after a time without practicing it or had some kind of exhaustive exercise, particularly eccentric exercise. To evaluate the effect of cryotherapy and laser therapy in response to muscle damage induced by eccentric exercise on the biceps muscle. This was a randomized clinical trial consisting of 60 female subjects. All subjects initially underwent an evaluation consisting of perimetry, measurement of pain sensation (via algometry and visual analogue scale), electromyography and dynamometry. Then the subjects performed an exercise protocol on the isokinetic dynamometer consisting of 2 sets of 10 eccentric elbow flexors contraction at 60 °/s. Completed this protocol, an intervention was held according to a previously random group distribution: control group (no intervention), cryotherapy group and laser therapy group. Finally, subjects were re-evaluated immediately and 48 hours after the intervention protocol, except for Visual Analogue Scale (VAS), which was also evaluated 24 hours after exercise. The circumference of the limb, the pain sensation (VAS and algometry), the muscle activation amplitude (via Root Mean Square - RMS), median frequency, peak torque normalized per body weight, average peak torque, power and work were analyzed. The median frequency immediately after the intervention protocol on the cryotherapy group was the only variable that showed inter and intra-group differences; the remaining variables showed only intragroup differences. The perimetry values did not change immediately after the protocol on the groups which underwent cryotherapy and laser therapy, however, there was an increase after 48 hours; algometry values decreased in all groups for 48 hours and the VAS values increased 24 and 48 hours also for all groups. Regarding RMS no significant change was observed. For dynamometry, peak torque normalized per body weight and average peak torque had a similar behavior, with a reduction in the post protocol that has remained after 48 hours. For the power and work, a decrease was observed immediately after the protocol with a further reduction after 48 hours. Cryotherapy and laser therapy does not alter the muscle damage response, except for the perimetry values immediately after exercise.